1988
DOI: 10.1161/01.atv.8.5.452
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenicity and carcinogenicity of high-arsenic artesian well water. Multiple risk factors and related malignant neoplasms of blackfoot disease.

Abstract: The objective of this study was to examine multiple risk factors and correlated malignant neoplasms of blackfoot disease (BFD), a unique peripheral vascular disease related to continuous exposure to high-arsenic artesian well water. A total of 241 BFD cases, Including 169 with spontaneous or surgical amputations of affected extremities, and 759 age-sex-resldence-matched healthy community controls were studied to explore the risk factors of BFD. Multiple logistic regression analysis showed that artesian well wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(117 citation statements)
references
References 6 publications
2
114
0
1
Order By: Relevance
“…The finding of a strikingly increased prevalence of macrovascular diseases observed in the arseniasis-endemic area compared with the nonendemic area is consistent with our previous findings of arsenic-induced atherosclerosis (Chen et al 1988bChiou et al 1997b;Tseng et al 1996;Wang et al 2002;Wu et al 1989). There have been few studies comparing the prevalence of specific vascular diseases in relation to arsenic exposure in diabetics and nondiabetics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The finding of a strikingly increased prevalence of macrovascular diseases observed in the arseniasis-endemic area compared with the nonendemic area is consistent with our previous findings of arsenic-induced atherosclerosis (Chen et al 1988bChiou et al 1997b;Tseng et al 1996;Wang et al 2002;Wu et al 1989). There have been few studies comparing the prevalence of specific vascular diseases in relation to arsenic exposure in diabetics and nondiabetics.…”
Section: Discussionsupporting
confidence: 92%
“…The water from a large proportion of artesian wells in these four townships had arsenic concentrations > 0.35 mg/L according to a national survey of more than 90% of wells in Taiwan (Chang et al 1991). This arseniasis-endemic area has been described in detail in a previous report (Chen et al 1988b). A total of 66,667 residents ≥ 25 years of age in the arseniasis-endemic area were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated familial patterns and genetic factors in development of arsenic health effects and metabolism. In Taiwan, a population-based study found that patients with blackfoot disease, an arsenic-induced peripheral vascular disease, were three times more likely to have a family history of blackfoot disease than community controls (23). However, exposure variation could account for this pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the lung cancer risk of smokers without arsenic in their water was about six times that of non-smokers. This, along with the vascular effects of both arsenic and smoking (Tseng et al, 1996;Engel et al, 1994;Chen et al, 1996Chen et al, , 1988Hertz-Picciotto et al, 2000) might suggest that those who have been exposed to arsenic in water should be advised not to smoke. However, since smoking kills nearly one in two persons without arsenic in their water, it hardly seems pertinent to point out that smokers who have arsenic in their water have even greater risks.…”
Section: Smokingmentioning
confidence: 99%